Effect of computerised training on cognition, sel Management and quality of life in elderly with type 2 Diabetes mellitus: a study protocol for a single blind Randomised controlled trial - Ms. SUMAM SUNNY; DR. AJITH S; DR.DHANESH KUMAR K.U (International Journal of Pharma and Bio Sciences, 2017)
The prevalence rate of type 2 diabetes mellitus in elderly population is 30.42% which is an immense sprouting public health burden adversely affecting quality of life and increasing workload on the health care system. Elderly people with type 2 diabetes mellitus have decreased cognition ability when correlated to elderly without diabetes. The adverse effects of lowered cognitive ability exert a huge negative impact on the self management abilities of elderly with type 2 diabetes mellitus which adversely affects the quality of life. Hence there is a need to find effective cognitive training interventions to postpone the cognitive compromise in elderly that can be used in everyday clinical settings. The objective is to determine the effects of computerised cognitive training on cognitive abilities, self management and quality of life in elderly with type 2 diabetes mellitus. The study design is a single blind randomized control study and the patients will be recruited from K.S Hegde Charitable hospital, Mangalore. All the participants will receive standard self management care treatment techniques in type 2 diabetes mellitus. The experimental group will receive additional 20 minutes of computerized cognitive training using Fit Brains software. Fit brains is a individualised cognitive training program which trains individuals through various exercises in the areas of short- and long-term memory, language, visual-spatial processing, reasoning and problem-solving, and calculation skills. The treatment will be given three times a week for two months. Outcome measure scores of Montreal cognitive assessment scale ,diabetes self management questionnaire and quality of life 36 will be taken before and after the treatment of 2 months in both experimental and control group. The statistical analysis will be done using SPSS software and p value of less than 0.05 will be considered significant. The study will be the first randomized control study that will assess the effectiveness of computerized cognitive training on cognition, diabetes self management and quality of life. Various cognitive training methods have been found effective in healthy elderly population but effects of cognitive training in self management, cognitive ability and quality of life of diabetic elderly is unknown The clinical trial registry number is CTRI/2017/02/007881.